Quest of Urban Growth Monitoring from Myth to Reality - Sheeba Afsar; Syed Jamil Hassan Kazmi; Sumaiya Bano (Journal of Basic & Applied Sciences, 2013)
The Earth’s surface is changing rapidly, mainly because of the anthropogenic interventions. At many point of times, these changes are local, regional, national, and even global in scale, interconnected both horizontally and vertically. Some changes have natural causes, such as earthquakes or floods. Other changes, such as urban expansion, agricultural intensification, resource extraction, and water resources development are examples of human-induced change that have significant impacts upon people, the economy and resources. As the urban growth in the world as major element of change, the appraisal and monitoring of these areas is a matter of great concern for a quality life of human beings. For this purpose, an appropriate and instantaneous technology is required to monitor the unwanted change. Hence, the main objective of this paper is to monitor the spatial extension of urban growth of the Metropolitan Karachi during 1955-2010 using different data sets and series of satellite imageries. In addition to that the growth corridors have also determined both in terms of magnitude and direction. The spatial change detected through successive satellite imageries has revealed a gigantic change from 1955 to 2010. The averageannual growth rate of the Metropolis has taken place at an outstanding 13.35 %. It has been also found that the increase in urban growth has been noted towards the East and West of the city mainly but due to rapid expansion of housing schemes in north-eastern part of the city an enormous urban growth has taken place there as well. The paper has also revealed the utility of the Geo-Informatics for the monitoring of urban growth.